15jährige Versicherungsstatistik zu Inzidenzen und Unfallhergangstypen von Kampfsportverletzungen im Landessportbund Rheinland-Pfalz - Raschka, C.; Parzeller, M.; Banzer, W. (Sportverletzung Sportschaden, 1999)
The primary intention of this study is the grouping of sports accidents, being described by the athletes in their own words in a classification system of specific accident classes with regard to specific motions and topography. The investigation is based on the data of the sports insurance Gerling-Konzern during a 15-year period in Rhineland Palatinate (1981-1995). The study is based on the insurance documents and clinical protocols if available. 137 accident protocols were related to this 15-year period including weight lifting (n = 1) and martial arts (n = 136). Listed in hierarchical order we received the following results: judo (n = 47), karate (n = 44), wrestling (n = 22), taekwondo (n = 9), boxing (n = 7), ju-jutsu (n = 5), fencing (n = 1) and aikido (n = 1). In accordance to accident types there were no sex related differences. As special preventive measures we suggest the use of protective mouthguards and solid glasses, proprioceptive training and physiological taping for knee, ankle and elbow joints.